TINGKAT PENGETAHUAN AKAN MEMPENGARUHI TINGKAT DEPRESI PENDERITA KANKER - Nilamsari, Nilamsari; Handayani, Nanik (Universitas Nahdlatul Ulama Surabaya, 2014)
Now, cervical cancer still becomes a reproductive health problem for the females in Indonesia. Cancer diagnosis is one of the stressors which may trigger the mental problems; the common problems which often occur are anxiety and depression Therefore, the purpose of this study was to find out the correlation between cervical cancer and depression level in cervical cancer sufferers found in Indonesian Cancer Foundation, located in Surabaya  The type of study was analytic-observational done by applying cross sectional approach. The population involved all women suffering from cervical cancer found in Indonesian Cancer Foundation, totally 20 people. 19 respondents fulfilling the criteria were taken as the samples by using simple random sampling technique. The instrument for collecting the data was the questionnaire of Back Depression Inventory. The data obtained before were analyzed by using Spearman?s Rank correlation test with the significance level ? = 0.05.  The result of study done to 19 respondents suffering from cervical cancershowed that half of them (47.4%) had a low level of knowledge about cervical cancer; and 44.4% had mild depression. Moreover, according to Spearman?s Rank correlation test, p = 0.024 < ? = 0.05 so that H0 was rejected describing that there was a correlation between cervical cancer and depression level in cervical cancer sufferers. The resume of this study was almost helf respondents in Indonesian Cancer Foundation had a low level of knowledge, and had mild depression. There fore the health workers was hoped usually to give informative support such as education, promotion even conseling to cervical cancer sufferers.